Evaluasi Penerapan Pengendalian Internal Atas Piutang (Studi Pada PT X) - Khoiriawati, Novi; Barokah, Zuni (Jurnal Akuntansi dan Ekonomika, 2019)
The credit sales strategy has the consequence of substantial business receivables. Increased receivables will have an impact on the company's liquidity and threaten the survival of the company which causes the company to go bankrupt. This study aims to evaluate the implementation of internal controls based on the COSO framework and  analyze the factors that inhibit the implementation internal controls of receivables at PT X. This study used qualitative. Data was collected through questionnaires based on Internal Control Questionnaire (ICQ), interviews, and documentation. The analysis technique is Champion (1990). The results of study showed that implementation of internal control over account receivables PT X has score above 71,21%. There are 9 weaknesses in the implementation of internal control over receivables at PT X. The results of this study are expected to provide information and input to PT X in optimizing the implementation of internal control over receivables.